No Country for Old Men: Restrictions on the Immigration of Elderly Family Members - Szigeti, Péter (McGill Law Journal / Revue de droit de McGill, 2023)
Immigration policies are aimed at young-to-middle-aged people, for good reasons. The exceptions are parental and grandparental immigration programs, designed to reunite yesterday’s immigrants and their young children with the (grand)parents who still live in the country of origin. (Grand)parental immigration has been an unquestioned facet of immigration law for the last century and a half. Elderly people are the least threatening immigrants: they rarely commit crimes, they are not conduits for further immigrant family members, and they are unlikely to fundamentally change the culture of the destination state. Yet the last few decades have seen an unprecedented and mostly unremarked assault on parental and grandparental immigration, with some rather shoddy economics as the only reason. Quotas have been lowered, required sponsorship amounts have been raised, health conditions have been made stricter, and family structures have been added to the list of criteria. This article looks at the tightening of immigration rules since the 1970s in three types of immigrant-receiving countries: traditional settler states, modern settler states, and liberal states which seek to discourage immigration. The article concludes that reasons, whether legal, political or economic, are lacking in both quantity and quality. The growing restrictions on elderly immigration are unjust and senseless, and should be reversed.